Distinctive EBV infection characteristics in children from a developing country. (April 2020) - Ferressini Gerpe, N.M.; Vistarop, A.G.; Moyano, A.; De Matteo, E.; Preciado, M.V.; Chabay, P.A.
Graphical abstract: Highlights: Epstein–Barr virus infection is characterized by low viral load in pediatric tonsils. Unlike IM, full viral latency pattern is almost absent in primary infected patients. Full latency pattern is displayed almost exclusively in healthy carriers. Few cases exhibited lytic cycle antigens; it may be a strategy to avoid immune system. The lack of symptoms in primary infection may be related to these characteristics. Abstract: Background: In developing countries, Epstein–Barr virus (EBV) infection is mostly asymptomatic in early childhood. EBV persistence may lead to different malignancies, such as B cell derived lymphomas. In Argentina, most children are seropositive at three years and an increased association between EBV and lymphoma was proved in children under 10 years old by our group. Objective: Our aim was to characterize EBV infection at the site of entry and reactivation of viral infection —the tonsils— in order to better understand the mechanism of viral persistence in pediatric patients. Methods: A cohort of 54 patients was described. We assessed specific antibodies profiles in sera; viral proteins presence by IHC on FFPE samples and EBV type from fresh tissue. Results: EBV type 1 was prevalent, mostly in the youngest patients. Asymptomatic primary infected patients presented higher viral loads and Latency 0/I or II patterns, whereas the Latency III pattern was observed mostly in healthy carriers. There were no differences between groups in the expression of viral lytic antigens. This study discloses new features in patients undergoing primary infection from a developing population. Low viral inoculum and restricted viral antigen expression may be responsible for the lack of symptoms in children from our country.